Range-Adapting Representation of Economic Value in the Orbitofrontal Cortex - Padoa-Schioppa, Camillo (Society for Neuroscience, 2009)
While making economic choices, individuals assign subjective values to the available options. Values computed in different behavioral conditions, however, can vary substantially. The same person might choose some times between goods worth a few dollars, and other times between goods worth thousands of dollars, or more. How does the brain system that computes values—the “valuation system”—handle this large variability? Here we show that the representation of value in the orbitofrontal cortex (OFC), an area implicated in value assignment during economic choice, adapts to the behavioral condition of choice and, more specifically, to the range of values available in any given condition. In the experiments, monkeys chose between different juices and their choice patterns provided a measure of subjective value. Value ranges were varied from session to session and, in each session, OFC neurons encoded values in a linear way. Across the population, the neuronal sensitivity (defined as the change in neuronal activity elicited by the increase in one value unit) was inversely proportional to the value range. Conversely, the neuronal activity range did not depend on the value range. This phenomenon of range adaptation complements that of menu invariance observed in a previous study. Indeed, the activity of each neuron adapts to the range values it encodes but does not depend on other available goods. Our results thus suggest that the representation of value in the OFC is at one time instantiative of preference transitivity (menu invariance) and computationally efficient (range adaptation).